GEN Y CONSUMER’S SOCIAL MEDIA COMMUNICATION, BRAND LOYALTY AND PURCHASING INTENTION IN MALAYSIA: INVESTIGATING THE MODERATING ROLE OF BRAND TRUST - Asma Abdurasak Ahmed; Norzehan Abu Bakar (Journal of Global Business and Management Review, 2021)
This research investigates the associations between social media communication (SMC), brand loyalty (BL) and brand trust (BT) and its influence on purchase intention (PI) of the Gen Y Consumers in Kuala Lumpur Malaysia. The study looked into the role of brand trust in moderating the relationship between social media communication, brand loyalty, and purchasing intention. The study adopted the quantitative research method. The population of the study consisted of Gen Y consumers, living in Malaysia. A sample size of 361 responses were collected by using the convenience sampling procedure. A structured survey approach was applied and the responses were collected by online mode through google forms. The statistical package for social science (SPSS) 23 was utilised for the analysis of the data. The results revealed that the SMC influence among the Gen Y consumers had a positive effect on PI. In addition, the association between BL, BT and PI was not significant. Equally, BT moderated the association between SMCand PI. The results can help marketers to grows effective promotion stratagems to improve SMC, build BL and trust particularly in the fast-food business in Malaysia.